Structural Design Optimization of Bellcrank 3 in the N219 Aircraft Flap Flight Control System Using the Finite Element Method - Hartini, Dwi; Bachtiar, Muhamad Irfan; Nugroho, Fajar; Anna Prattiwi, Elisabeth Anna; Santoso, Djarot Wahju (Vortex, 2026)
The flap control system is a critical subsystem in aircraft that directly affects aerodynamic performance and flight safety. One of the key mechanical components in this system is the bellcrank, which functions to transmit and redirect loads from the actuator to the flap mechanism. In this study, structural optimization of bellcrank 3 in the flap control system of the N219 aircraft was performed using the Finite Element Method (FEM). Three design configurations were analyzed, namely the base model, optimization model 1 with thickness reduction, and optimization model 2 with the addition of holes in non-critical areas. Structural evaluation was conducted based on mass reduction, displacement, von Mises stress, and margin of safety (MS). The simulation results show that both optimization approaches successfully reduce structural mass compared to the base model. Optimization model 1 achieves the largest mass reduction but results in higher stress levels and lower margin of safety. Optimization model 2 provides a more balanced structural performance, with stress, displacement, and margin of safety values comparable to the base model while maintaining mass reduction. All analyzed configurations exhibit positive margin of safety values, indicating that the structures remain safe under the applied operational loads. Based on the overall structural performance, optimization model 2 is considered the most suitable design for application in the flap control system of the N219 aircraft.